KUALITAS PELAYANAN PEMBUATAN SURAT KETERANGAN CATATANKEPOLISIAN - Sangidun E.21110108 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this research is the creation of service quality manufacture Police Notes (SKCK) not referring to the principles of service which includes simplicity, clarity, certainty of time, and completeness of the facilities / infrastructure. Besides, the attitude of staff in providing services can not maintain a working relationship and to create satisfaction to the people it serves. For example, time in service efficiency, ease of service, and the justice ministry. The results showed that the quality of service creation Police Notes (SKCK) in Pontianak Police can be quite good. It is evident from some of the interview informants who stated quite good, especially on indicators of reliability and readiness officer. Whereas on other indicators such as keberwujudan, empathy and competencies they informant who expressed less satisfaction. Addressing the phenomenon of officers must fully understand the duties and functions especially those serving in ministry SKCK space. Increased knowledge and skills need to be upgraded constantly, in order that the assessment is not satisfied with the image and quality of police services provided by the police can be minimized as small as possible. Besides the public to understand more about the advantages of having SKCK, and understand the processes and procedures in making SKCK as previously described. Whatever the police do is to grow in self-awareness about security sought by the authorities for his own people, and do not make the national police as enemies but rather as people of the community security guard. To reinforce the issue of alternative solutions Police agencies are expected to fully support the officers or the national police in an effort to improve its image in the eyes of society, especially in SKCK service delivery, provision of facilities in the form of facilities and infrastructure to facilitate the national police in carrying out the duties to the fullest.Keywords: Quality, Service, manufacture, Police Notes